A Literature Review of the STEAM Approach in Enhancing High School Students’ Understanding of Renewable Energy Concepts - Shofi Shofiah; Muhammad Minan Chusni; Adam Malik (Jurnal Ilmiah Pendidikan Fisika, 2026)
Creative approaches to physics education must be continuously developed to enhance conceptual understanding of renewable energy topics. An ideal learning process accelerates the need for high-quality resources through contextual and integrated methods. Renewable energy has become a global issue that necessitates a significant role in education. The STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach is considered capable of improving both skills and conceptual understanding in learning. This study aims to explore the STEAM approach in relation to educational needs for fostering innovation. The research method employs a literature review, examining theoretical references relevant to enhancing conceptual understanding and focusing on an analysis of reputable scientific articles (2015–2025). The inclusion criteria are based on the effectiveness of STEAM implementation at the secondary education level. The results indicate that the integration of engineering and arts components is able to reduce the abstraction of renewable energy concepts. In conclusion, STEAM not only improves cognitive understanding but also enhances students’ sustainability literacy. The implications of this study provide strategic recommendations for educators in developing contextual modules. This research is expected to assist educators in designing effective learning and preparing students for a sustainable future.